Analysis of financial statements, cash flow and dividend policy on stock prices in food and beverage sector companies listed on the indonesia stock exchange for the 2018-2020 period - Verawati Verawati; Robinhot Gultom; Ella Silvana Ginting (Indonesia Accounting Research Journal, 2022)
This study aims to determine and analyze the effect of Return on Equity, Operating Cash Flow and Dividend Per Share on a modest and partial basis on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. The population in this study amounted to 34 companies. The sample sampling method uses pursose sampling techniques, and the number of samples obtained is as many as 12 companies. The data testing method used is multiple linear regression analysis. Based on the results of data testing, simultaneously Return on Equity, Operating Cash Flow and Dividend Per Share have a significant effect on stock prices in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. Meanwhile, partially dividend per share has a significant effect on stock prices positively in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. However, the Return on Equity did not have a significant effect on the share price positively in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period. And Operating Cash Flow did not have a significant effect on stock prices negatively in food and beverage sector companies listed on the Indonesia Stock Exchange for the 2018-2020 period